2007
DOI: 10.1002/jso.20821
|View full text |Cite
|
Sign up to set email alerts
|

Routine drainage after thyroid surgery—A meta‐analysis

Abstract: Thyroidectomy is a common surgical procedure. The results of some clinical trials suggest that routine drainage does not offer advantages, but the evidence is not strong either in favor of or against this intervention. The effect of routine drainage compared to no drainage in patients subject to thyroidectomy was measured using a meta-analysis. After an extensive literature review, suitable randomized clinical trials were selected for analysis. Outcome measures included the comparative incidence of neck hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
44
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 20 publications
6
44
0
1
Order By: Relevance
“…[2][3][4][5][6] Furthermore, no difference in perioperative complications (seroma, hematoma, hemorrhage) was found among the 3 types of surgical procedures (hemithyroidectomy, total thyroidectomy, total thyroidectomy with CND) in either group. There was no major bleeding in either group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6] Furthermore, no difference in perioperative complications (seroma, hematoma, hemorrhage) was found among the 3 types of surgical procedures (hemithyroidectomy, total thyroidectomy, total thyroidectomy with CND) in either group. There was no major bleeding in either group.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have demonstrated that drainage after uncomplicated thyroid surgery, including total thyroidectomy, lobectomy and subtotal thyroidectomy, does not decrease the rate of complications related to postoperative bleeding. [2][3][4][5][6][7] Most hematomas are clinically apparent within 2-4 hours after surgery, and some occur 2-48 hours postoperatively. The diagnosis of wound hematoma is made by observing the neck and noticing a progressive collection under the skin or airway symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For minimizing the risk for hematoma and seroma, the formation of dead space should be reduced, in addition to effective bleeding control. In the literature, in the studies conducted on the necessity of drain usage, drained and non-drained patients were compared in terms of postoperative hematoma, seroma, and the amount of the liquid accumulation in the thyroidectomy bed, and similar results were reported for both groups (1,2). Nevertheless, many surgeons still use drain after thyroidectomy (1)(2)(3).…”
Section: Introductionmentioning
confidence: 96%
“…In the literature, in the studies conducted on the necessity of drain usage, drained and non-drained patients were compared in terms of postoperative hematoma, seroma, and the amount of the liquid accumulation in the thyroidectomy bed, and similar results were reported for both groups (1,2). Nevertheless, many surgeons still use drain after thyroidectomy (1)(2)(3). Another way of reducing post-thyroidectomy dead space volume is to perform pressure dressing with drainage (3).…”
Section: Introductionmentioning
confidence: 98%